Rocky, a fighter and Dominga, a paper collector! The intersections of monuments that resist! - Nunes, Fabíola Fraga; Miranda, Giuliano de; Cirillo, Aparecido José (Revista do Colóquio, 2024)
This article discusses aspects of public art and intercultural relations conceived from the perspective of a public monument, one located in Philadelphia, in homage to the character from the film Rocky: a fighter (1976), and another to Dona Dominga, located in Vitória. Balboa and Dominga are immigrants and belong to an excluded social class. We establish some connections between the two monuments, insofar as, beyond the physical work, the dialogue regarding the public document and its function of amplifying narratives is strengthened, as well as a fertile territory for debates about history and the human condition, seen through the ethnic-racial prism common to both works in different social contexts.